Beamforming Techniques for the Frequency Diverse Array - Youssef, Yazan (2020)
A Master of Science thesis in Electrical Engineering by Yazan Youssef entitled, “Beamforming Techniques for The Frequency Diverse Array”, submitted in May 2020. Thesis advisors are Dr. Hasan Mir and Dr. Lutfi Albasha. Soft copy is available (Thesis, Approval Signatures, Completion Certificate, and AUS Archives Consent Form).